Screen interpretation of Franz Kafka's novel 'The Trial': Interaction of the author with the script writer and film director - K.V. Arjantzeva (Ученые записки Казанского университета: Серия Гуманитарные науки)
Harold Pinter is a British writer, playwright, poet and screenwriter, and the recipient of the Nobel Prize in Literature in 2005, whose artistic genius is familiar to the Russian reading audience. The main problem covered in his works is the problem of disengagement, alienation, and disunity, which has become the attribute of the modern world. This peculiarity of H. Pinter's world outlook must have determined his interest in the novel 'The Trial' by Franz Kafka, the Austrian writer. Existential guilt, inherently attributed to the senior bank clerk Joseph K., in F. Kafka's novel and the motif of persistent imminent menace in H. Pinter's drama (especially, in “The Birthday Party”, which is the most remarkable example of F. Kafka's plot interpretation elaborated by H. Pinter), represent the philosophical and psychological basis of text architectonics which unites the two authors. In the context of the original literary text, such a specific feature of F. Kafka's aesthetics as visualization of the space and usage of various visual effects in the text is of great interest due to the basis it creates for translation into the language of cinematography. The aim of this study is to identify and classify the peculiarities of the screen interpretation of the novel at the following two levels: the screenplay by H. Pinter and the screen version of the novel by David Hugh Jones, the film director. In accordance with this aim, the work has been conditionally divided into two parts. In the first part, the interpretation of the novel in the form of a screenplay written by H. Pinter has been analyzed. Here, the main principles of translation from one author's language into the other's one have been identified. Furthermore, some examples endorsing the visual character of F. Kafka's prose, which allowed to adjust “The Trial” to the script text, have been provided. In the second part of the paper, an attempt has been made to identify the peculiarities of the film based on the screenplay by H. Pinter. The paper shows certain devices employed by the screenwriter and the film director to make an interpretation of the original text into the cinematographic language.